2016
DOI: 10.1155/2016/4195762
|View full text |Cite
|
Sign up to set email alerts
|

“I Always Worry about What Might Happen Ahead”: Implementing Safer Conception Services in the Current Environment of Reproductive Counseling for HIV-Affected Men and Women in Uganda

Abstract: Background. We explored healthcare provider perspectives and practices regarding safer conception counseling for HIV-affected clients. Methods. We conducted semistructured interviews with 38 providers (medical and clinical officers, nurses, peer counselors, and village health workers) delivering care to HIV-infected clients across 5 healthcare centres in Mbarara District, Uganda. Interview transcripts were analyzed using content analysis. Results. Of 38 providers, 76% were women with median age 34 years (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
0
36
0
1
Order By: Relevance
“…Factors affecting SCS availability from the individual or couple’s perspective included lack of awareness about safer conception services [20, 22, 33, 3642] and limited integration of services for sexual and reproductive health into HIV care [4345]. Few patients discussed fertility goals with providers, and discussions around pregnancy focused on maternal and child health and not on sexual HIV transmission [3941, 46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors affecting SCS availability from the individual or couple’s perspective included lack of awareness about safer conception services [20, 22, 33, 3642] and limited integration of services for sexual and reproductive health into HIV care [4345]. Few patients discussed fertility goals with providers, and discussions around pregnancy focused on maternal and child health and not on sexual HIV transmission [3941, 46].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were qualitative assessments of healthcare providers and people living with HIV or serodiscordant couples. Several studies found that providers rarely initiated discussion of fertility intentions and reproductive goals with HIV-affected clients during visits [24, 39, 41, 42, 46, 50, 58, 65]. When fertility intentions were assessed, usually only the woman’s reproductive goals were discussed and not the man’s or couples [58, 61].…”
Section: Resultsmentioning
confidence: 99%
“…Many recent safer conception studies and public programmes have shown good uptake of safer conception strategies, including ART and PrEP [25][26][27][28][29]. To the best of our knowledge, ours is the first study to estimate the effectiveness of a safer conception intervention on HIV transmission risk.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, provider efforts tend to be limited to maternal health and prevention of vertical transmission of HIV [10,12,14]. As a result, patients have limited knowledge of safer conception methods, which limits their uptake of safer conception strategies and their ability to reduce HIV transmission risks [1517].…”
Section: Introductionmentioning
confidence: 99%